MLL2 mutation detection in 86 patients with Kabuki syndrome: a genotype–phenotype study. (26th April 2013) - Makrythanasis, P; van Bon, BW; Steehouwer, M; Rodríguez‐Santiago, B; Simpson, M; Dias, P; Anderlid, BM; Arts, P; Bhat, M; Augello, B; Biamino, E; Bongers, EMHF; et al.
Abstract : Recently, pathogenic variants in the MLL2 gene were identified as the most common cause of Kabuki (Niikawa–Kuroki) syndrome (MIM#147920). To further elucidate the genotype–phenotype correlation, we studied a large cohort of 86 clinically defined patients with Kabuki syndrome (KS) for mutations in MLL2 . All patients were assessed using a standardized phenotype list and all were scored using a newly developed clinical score list for KS (MLL2‐Kabuki score 0–10). Sequencing of the full coding region and intron–exon boundaries of MLL2 identified a total of 45 likely pathogenic mutations (52%): 31 nonsense, 10 missense and four splice‐site mutations, 34 of which were novel. In five additional patients, novel, i.e. non‐dbSNP132 variants of clinically unknown relevance, were identified. Patients with likely pathogenic nonsense or missense MLL2 mutations were usually more severely affected (median 'MLL2‐Kabuki score' of 6) as compared to the patients without MLL2 mutations (median 'MLL2‐Kabuki score' of 5), a significant difference (p < 0.0014). Several typical facial features such as large dysplastic ears, arched eyebrows with sparse lateral third, blue sclerae, a flat nasal tip with a broad nasal root, and a thin upper and a full lower lip were observed more often in mutation positive patients.